The proteome of circulating extracellular vesicles and their functional effect on platelets vary with the isolation method - Eva M. Fernández-Sáez; Susana B. Bravo; Carmen Pena; Ángel García (Scientific Reports)
Abstract Extracellular vesicles (EVs) play a crucial role in cell-to-cell communication and serve as a source of biomarkers in several pathologies. In this study, we aimed to characterize plasma-derived EVs isolated by ultracentrifugation (UC) or size exclusion chromatography (SEC) to define the best method for proteomic and functional studies. EVs characterization included nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM), detection of biomarkers by western blotting, and quantitative proteomic analysis. SEC-EVs samples had higher particle and protein concentration, particle-to-protein ratio, and smaller size compared to UC-EVs. A total of 171 proteins were identified through Sequential Window Acquisition of All Theoretical Mass Spectra (SWATH-MS) analysis, with 11 increased in SEC-EVs and 5 in UC-EVs. The proteins increased in UC-EVs are complement proteins and immunoglobulins, while proteins increased in SEC-EVs are apolipoproteins and proteins present in the extracellular space. Functional studies with EVs from activated platelets confirmed that EVs isolated by SEC exacerbate platelet aggregation, whereas there was no effect induced by UC-EVs. The latter suggests that EVs obtained by SEC seem more suitable for platelet-related functional studies compared to those obtained by UC. The results presented pave the way for future clinical orientated studies involving plasma-derived EVs.